Rancang Bangun Sistem Informasi Pelayanan Posyandu Berbasis Web Pada Posyandu Matahari 17 Di Bumi Asri Tangerang - Sri Mulyati (Universitas Muhammadiyah Tangerang, 2023)
Data processing at Matahari 17 Posyandu uses the manual method, namely using books and some papers collected in one archive box. If the posyandu data is collected in large quantities and in a short time, the processing of the data and the results to be obtained take quite a long time, so that it seems slow in processing the data. The data collected at the posyadu is quite a lot, namely data on the implementation of immunization, weighing of babies and others related to posyandu activities. It is difficult to verify old data, and it is difficult if the paper or book used is damaged. In dealing with this problem, namely creating an information system that is made digitally. This system is paperless using two methods, namely the SWOT analysis method and the Extreme Programming system development method. This research resulted in a fairly efficient and effective Posyandu Service Information System. With this information system, it can make it easier for Posyandu officers to record and store data that can be stored safely. The Posyandu Information System makes it very easy to collect and process it. Keywords: Services, Posyandu, Immunization, Information Systems, SWOT, Extreme Programming